# Calculus - repost

posted by .

Find the derivative of F(x)= integral from -2 to x of sqrt(t^3+8)dt?

My answer: sqrt(x^3+8)? Is this right?

• Calculus - repost -

Yes, the value of the function at the upper limit where t = x.

## Respond to this Question

 First Name School Subject Your Answer

## Similar Questions

1. ### Calculus

Graph the curve and find its exact length. x = e^t + e^-t, y = 5 - 2t, from 0 to 3 Length = Integral from 0 to 3 of: Sqrt[(dx/dt)^2 + (dy/dt)^2] dx/dt = e^t - e^-t, correct?
2. ### calc check: curve length

Find the length of the curve y=(1/(x^2)) from ( 1, 1 ) to ( 2, 1/4 ) [set up the problem only, don't integrate/evaluate] this is what i did.. let me know asap if i did it right.. y = (1/(x^2)) dy/dx = (-2/(x^3)) L = integral from a …
3. ### Calculus

1) Find the derivative with respect to x of Integral from 1 to X^3 of sqrt( 1 + t²) dt I got sqrt( 1 + X^6) * 3x². Is that right?
4. ### Calculus

Find the volume of the solid whose base is the region in the xy-plane bounded by the given curves and whose cross-sections perpendicular to the x-axis are (a) squares, (b) semicircles, and (c) equilateral triangles. for y=x^2, x=0, …
5. ### Calculus

Find the derivative of F(x)= integral from -2 to x of sqrt(t^3+8)dt?
6. ### Calculus

Evaluate the indefinite integral: 8x-x^2. I got this but I the homework system says its wrong:sqrt((-x-8)x)/(2*sqrt(x-8)*sqrt(x))*(((sqrt(x-8)*(x-4)*sqrt(x))-32*log(sqrt(x-8)+sqrt(x))
7. ### Calculus 2 (Differential Equation)

How would you solve the following problem explicitly?
8. ### Math - Calculus

Find the area of the surface of revolution generated by revolving the curve y = 3 sqrt (x), 0 <= x <= 4, about the x-axis. Okay, so I've set up the integral like this: 2pi ∫[0,4] (3 sqrt (x))(sqrt(1+(1/4x)))dx Which is coming …
9. ### Calculus

Find the derivative of the integral from 2 to 5x of (sqrt(1 + u^2))/u. My answer: (sqrt(1 + 25x^2)/5x) * 5﻿﻿﻿﻿
10. ### Calculus - Integrating

Question: ∫(x^2)/sqrt(x^2+1) u=x^2+1 , x^2= u-1, du=2xdx ∫(u-1)/sqrt(u) , expand ∫u/sqrt(u) - 1/sqrt(u) Integrate: 2/3(u^(3/2)) - 2u^(1/2) + c My answer: [ 2/3(x^2+1)^(3/2) - 2(x^2+1) + c ] When I took the derivative of this …

More Similar Questions